Organizations Building Resilient Students: HIMA UIN Jambi Capacity Building Reflection Program - Billy Febrima Hidayat; Zulfadli; Asrinaldi; Dewi Anggraini; Tamrin; Irawati; Doni Hendrik; Andri Rusta (Amalee: Indonesian Journal of Community Research and Engagement, 2026)
Student organizations are integral to the campus political ecosystem, playing a crucial role in planning, decision-making, and allocating roles and interests within the academic environment. However, weak institutional capacity often leaves student organizations trapped in ceremonial activities without a sustainable development direction. This article reflects on the implementation of a capacity-building program for the Student Association (HIMA) of the Faculty of Sharia at the Sultan Thaha Saifuddin State Islamic University of Jambi, as an effort to strengthen the political planning for student organization development. The service program was implemented through a participatory approach, using lecture-discussion methods, focus group discussions (FGDs), simulations, and discovery learning, to enhance HIMA administrators' ability to formulate organizational visions, develop strategic plans, and collectively and accountably manage work programs. The reflection results indicate that capacity building plays a crucial role in fostering organizational political awareness, particularly in understanding the relationships among leadership, decision-making, and program sustainability. This capacity-building encourages student organizations to be more responsive to internal campus issues and more adaptive to broader social dynamics. This article emphasizes that capacity building is a political instrument for student organization development, thereby strengthening HIMA's position as an actor in planning, implementing, and controlling campus-level policies.